Analysis of pullout behavior of single steel fibers embedded in concrete using phase‐field modeling. Issue 1 (17th December 2018) - Pise, Mangesh; Brands, Dominik; Gebuhr, Gregor; Schröder, Jörg; Anders, Steffen
Abstract: In this contribution, a constitutive framework of elasto‐plastic phase‐field model for fracture is applied to simulation of pullout test of single steel fiber embedded in concretes and compare it to the experimental results. For the description of the mechanical behavior the Drucker‐Prager plasticity model is used. The aim is to examine the pullout behavior of a single steel fiber and its influence on the overall material behavior. Therefore, the mechanical behavior of concrete is studied in experimental single fiber pullout test. The predictive capability of the above mentioned model is analyzed in detail by simulating a single fiber pullout test and compared against the experimental data.